TRACING OF VARIABILITIES WITHIN A GEOLOGICAL BARRIER BY MOLECULAR ORGANIC GEOCHEMISTRY. CASE OF THE CALLOVO-OXFORDIAN SEDIMENTARY SERIES IN THE EAST OF THE PARIS BASIN (FRANCE) - Hautevelle Y.; Michels R.; Elie M.; Trouiller A.; Malartre F. (My University, 2007)
The Callovo-Oxfordian claystones located at 500 m depth at Bure (Meuse, France) are currently being investigated by Andra (the French National Radioactive Waste Management Agency) for testing the feasibility of long-term and deep geological nuclear waste disposal. In order to evaluate its potential as a geological barrier, it is very important to study, assess and describe its physico-chemical variability. The molecular biomarker composition of 150 samples of these claystones and their surrounding limestones carry diverse information on the sources of the sedimentary organic matter, the chemistry of the depositional environment, the preservation and diagenesis conditions. It also allows assessing the degree of lateral and vertical variability of the organic matter within these sedimentary series. The abundance of unsaturated biomarkers, the distribution of steroids and hopanoids and CPI values >2 prove the thermal immaturity of the organic matter. The co-occurrence of plankton, bacteria and land plant biomarkers indicate that the organic matter is a mixture of marine and continental contributions. The data also reveal that the organic matter was deposited under oxic and open-sea conditions except for a brief event of photic zone anoxia at the beginning of the Middle Callovian. In the claystones, the geosynthesis of diasterenes is favored to the detriment of the formation of steranes, especially in smectite-rich levels, and the organic matter is rapidly isolated from oxidizing then reducing conditions after the deposition due to the protective effect of clays. On the scale investigated, the claystones are characterized by a unique molecular facies and are thus homogenous from their organic content point of view. Yet, detailed investigation of specific molecular families indicates changes related to major claystone-limestone transitions. The homogeneity of these claystones can be explained by the paleogeographic position of their depositional setting and the plane and sub-horizontal paleotopography on which they were deposited. This study demonstrates the efficiency of organic geochemistry in the assessment of the variability of geological barriers. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Oxfordian; Callovian; Mesozoic::Jurassic::Upper::Oxfordian; Мезозой::Юрская::Верхний::Оксфордский; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский